(untitled) (Al-Academy, 2025)
In recent years, the world has faced significant challenges, most notably the COVID-19 pandemic and various economic crises that have impacted many aspects of life. Specifically, the Palestinian people face additional challenges due to the practices and restrictions imposed by the Israeli occupation, including efforts to undermine and restrict the educational process. This study focuses on exploring the challenges faced by students of the Faculty of Fine Arts at An-Najah National University within the framework of electronic and blended learning systems. The researcher designed a questionnaire specifically for this purpose, which was distributed to a sample of students. The collected data was analyzed using the Statistical Package for the Social Sciences (SPSS). The study aimed to identify the challenges and realities of electronic and blended learning in the Faculty of Fine Arts, emphasizing the main obstacles students face in adopting this educational approach. These challenges include the pressures and restrictions resulting from the Israeli occupation, as well as technological and logistical difficulties. The research concluded with several findings and recommendations, the most notable being that electronic and blended learning have significantly contributed to maintaining the continuity of the educational process during the COVID-19 pandemic and after October 7th. Among the key recommendations were improving the technological infrastructure and training students in the effective use of electronic learning tools.